Rapid and automatic exposure control technique for high dynamic range in fringe projection profilometry - Ong, Jun Han (Nanyang Technological University, 2024)
This study undertakes the task of finding and implementing a rapid, automatic, and adjustable high dynamic range (HDR) algorithm for a developed Fringe Projection Profilometry (FPP) software. Literature relevant to this topic and principles necessary for the understanding of the task was first reviewed, followed by the analysis of a rapid and automatic HDR algorithm developed for another FPP software. This algorithm was implemented, and experimentation was carried out to seek out possible improvements. Further experimentation was done to compare the results of the original algorithm to the proposed improved algorithm. Through the analysis of the results gathered, it was concluded that the proposed algorithm not only satisfied the criteria of being rapid, automatic, and adjustable, but also performed better than the original algorithm. Finally, limitations of the study and recommendations were also analysed and discussed to close up the study.